From Satis House to Newgate: Manipulation and Repression in the Adaptation of Great Expectations by Julian Jarrold - Claudia Cao (Between, 2012)
This article analyzes a serial of Great Expectations in two parts directed by Julian Jarrold for the BBC in 1999. Through the semiotic approach proposed by Nicola Dusi in his essay Il cinema come traduzione. Da un medium all’altro (2003), this paper wants to highlight the translation strategies employed in the target text in comparison with the hypotext. The aim of this article is to show how the dominant isotopies – Pip’s repression and manipulation – are figurativized in the representation of the main places of power in the adaptation: Satis House, Little Britain and Newgate.